A study of fracture lines distribution characteristics in complete articular fractures of the patella - Wang, Xiong; Zi, Shuming; Wei, Wenqiang; Yao, Qiang; Cao, Liehu (Frontiers in Surgery, 2023)
The objective of this study was to unveil the characteristics of fracture lines distribution and explore its clinical significance of complete articular fractures of the patella. Methods: A consecutive series of image data from 88 patients with complete articular patella fractures were retrospectively included. Three-dimensional reconstruction images of the patella fractures were collected and created.Subsequently, these reconstructed images were visually overlaid onto a standard anterior and posterior patella template. The fracture lines were then identified, traced onto the template, and utilized to generate patella fracture maps. Furthermore, the incidence rate of patella fracture lines involving the distal pole was analyzed. Results:The maps depict the fracture lines of complete articular patella fractures. For simple and complex patella fractures, the primary fracture lines primarily converge within the Middle and Lower regions, exhibiting a transverse pattern. Conversely, the primary fracture lines in comminuted patella fractures are randomly dispersed across the patella. Examining the maps, approximately 63.6% (56/88) of complete articular patella fractures exhibited involvement of the distal pole in the anterior view, while 48.9% (43/88) displayed distal pole fractures in the posterior view. The incidence of distal pole injury increased progressively with the severity of patella fractures.The patterns and distribution of fracture lines in cases of complete articular patella fractures are prominently illustrated on the constructed fracture maps.Familiarity with these common characteristics of complete articular patella fracture, especially with the distal pole injury, can aid surgeons in developing preoperative planning, executing surgical strategies effectively, and reducing inappropriate treatment.